“Disposable” Labourer vs. Active Learner: Learning for Foreign Contingent Workers - Romee Lee (Adult Education Research Conference, 2004)
This paper argues for the need to conceptualize foreign contingent workers as legitimate adult learners. By looking critically at adult learning for these workers we can begin to discuss the importance of supported adult learning. This focus contributes to the formation of a just society where every group of learners’ communicative actions are supported and not infringed upon by oppressive structural power.